2021
DOI: 10.11613/bm.2021.030703
|View full text |Cite|
|
Sign up to set email alerts
|

Post-GDPR survey of data protection officers in research and non-research institutions in Croatia

Abstract: Introduction General Data Protection Regulation (GDPR) focuses on important elements of data ethics, including protecting people’s privacy, accountability and transparency. According to the GDPR, certain public institutions are obliged to appoint a Data Protection Officer (DPO). However, there is little publicly available data from national EU surveys on DPOs. This study aimed to examine the scope of work, type of work, and education of DPOs in institutions in Croatia. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Without clear appointment parameters, institutions were able to appoint anyone as DPO, just to fulfil a legal obligation. We found that the majority (92%) of surveyed DPOs in our study (Mladinić et al 2021) were already employed by their institutions when they were appointed as a DPO. Indeed, such an appointment strategy was the easiest solution for institutions.…”
Section: Dpos and Ethical Researchmentioning
confidence: 70%
See 3 more Smart Citations
“…Without clear appointment parameters, institutions were able to appoint anyone as DPO, just to fulfil a legal obligation. We found that the majority (92%) of surveyed DPOs in our study (Mladinić et al 2021) were already employed by their institutions when they were appointed as a DPO. Indeed, such an appointment strategy was the easiest solution for institutions.…”
Section: Dpos and Ethical Researchmentioning
confidence: 70%
“…Furthermore, our study (Mladinić et al 2021) showed that only around thirty percent of DPOs claimed to have an ethics committee in their institution where they worked. From those which indicated having an ethics committee in their institution, only a few DPOs received some official request or were contacted by their institutional ethics committee and the majority was not involved in that committee's work in any way.…”
Section: Dpos and Ethics Committeesmentioning
confidence: 75%
See 2 more Smart Citations
“…Very few research studies can be found on the topic of data protection in the EU. Recently, we published a survey among data protection officers (DPOs), examining the scope of work, type of work, and education of DPOs in institutions in Croatia [ 3 ]. However, when searching for studies on DPAs, we were unable to find any research reports that analyzed how different DPAs handle issues and complaints regarding data protection and their workload before and after the introduction of GDPR.…”
Section: Introductionmentioning
confidence: 99%